2019
DOI: 10.1038/s41593-018-0332-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy inhibits amyloid-β and tau pathology and reverses cognitive deficits in models of Alzheimer’s disease

Abstract: Accumulation of damaged mitochondria is a hallmark of aging and age-related neurodegeneration, including Alzheimer’s disease (AD). The molecular mechanisms of impaired mitochondrial homeostasis in AD are being investigated. Here we provide evidence that mitophagy is impaired in the hippocampus of AD patients, in induced pluripotent stem cell-derived human AD neurons, and in animal AD models. In both amyloid-β (Aβ) and tau Caenorhabditis elegans models of AD, mitophagy stimulation (through NAD+ supplementation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

42
1,170
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 1,234 publications
(1,216 citation statements)
references
References 66 publications
42
1,170
1
3
Order By: Relevance
“…Mitophagy is a regulated process that involves the degradation of damaged mitochondria by lysosomes. This process plays an important role in mitochondrial homeostasis, neuroprotection, and even healthy longevity in laboratory animal models [36, 37]. While we have characterized mitophagy in the CSB m/m mice [19], the changes of mitochondrial morphology and mitophagy in the animal models with CSA mutation or CSA/CSB double mutations are not known.…”
Section: Resultsmentioning
confidence: 99%
“…Mitophagy is a regulated process that involves the degradation of damaged mitochondria by lysosomes. This process plays an important role in mitochondrial homeostasis, neuroprotection, and even healthy longevity in laboratory animal models [36, 37]. While we have characterized mitophagy in the CSB m/m mice [19], the changes of mitochondrial morphology and mitophagy in the animal models with CSA mutation or CSA/CSB double mutations are not known.…”
Section: Resultsmentioning
confidence: 99%
“…This loss of connectivity is thought to be responsible for the early cognitive defects characterizing AD patients including defective learning and memory (Sheng et al, 2012;Terry et al, 1991). Recently, mitochondrial remodeling and dysfunction in PNs have emerged as a prominent cellular phenotype in AD (Cho et al, 2009;Fang et al, 2019;Wang et al, 2009a;Wang et al, 2009b;Zhang et al, 2016). However, whether this structural remodeling of dendritic mitochondria is causally linked to excitatory synaptic loss was unknown, in part because the molecular mechanism mediating Aβ42o-dependent mitochondrial remodeling are currently unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Results from our lab as well as others demonstrated that in neurons, Aβ42o over-activates AMP-activated kinase (AMPK) in a Calcium/calmodulin Kinase Kinase protein 2 (CAMKK2)-dependent manner and preventing CAMKK2 or AMPK over-activation either pharmacologically or genetically protects hippocampal neurons from Aβ42o-dependent synaptic loss in vitro and in the hAPP SWE, IND transgenic mouse model (J20) in vivo (Ma et al, 2014;Mairet-Coello et al, 2013;Son et al, 2012;Thornton et al, 2011). Importantly, AMPK is over-activated in the brain of AD patients where catalytically active AMPK accumulates in pyramidal neurons of the cortex and hippocampus (Fang et al, 2019;Vingtdeux et al, 2011). In non-neuronal cells, AMPK is a key metabolic sensor that is catalytically activated upon increasing levels of AMP/ADP (when ATP levels drop) and regulates various downstream effectors involved in maintaining mitochondrial integrity in part via two recently identified downstream effectors: mitochondrial fission factor (MFF) and Unc-51 like autophagy activating kinases 1/2 (ULK1/2) (Egan et al, 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…Mitophagy specifically has been proposed to contribute to several neurodegenerative diseases 18 . Evidence of early mitophagy induction and dysfunction has been observed in AD brains and in cells derived from patients with familial and sporadic forms of AD, which may exacerbate mitochondrial oxidative stress 12, 1922 .…”
Section: Mainmentioning
confidence: 99%